If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(-1r + -1) = 4 Reorder the terms: 3(-1 + -1r) = 4 (-1 * 3 + -1r * 3) = 4 (-3 + -3r) = 4 Solving -3 + -3r = 4 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -3r = 4 + 3 Combine like terms: -3 + 3 = 0 0 + -3r = 4 + 3 -3r = 4 + 3 Combine like terms: 4 + 3 = 7 -3r = 7 Divide each side by '-3'. r = -2.333333333 Simplifying r = -2.333333333
| z^2-14x=-40 | | 30=a+(2a+3)+(a+7) | | 3(2x+5)=4x+9 | | (24x-2)=(25x-8) | | 3(2x+5)=4x+8 | | 8x^2+13=213 | | X^4=.25 | | 140-x+40=180 | | 4(s+1.6)=-3s-1.2 | | 2(m-1)=3 | | 9a^2-6a+24=0 | | -3(4x-5)=-10 | | 80=10x+(x-1) | | 5xc=570 | | X+x*3= | | 7a-3=3A | | -23/-17 | | 197+2h=977 | | 2x+6x-9+4=3x-9+3 | | (5x-1)=(3x+1) | | -2a=3-a | | 5-x/38 | | 4(x^2+21x-280)=0 | | 10y^2+32y=0 | | -16x^2+32x-48=0 | | 10x-5/3=6x-5/2 | | 2x+6x-8+4=3x-9+3 | | (x-3)(x+4)=-30 | | 5+3x^2=18 | | -2(2x+3)=4 | | 4-x/56 | | X^3-2x^2+7x-14=equation |